2020
DOI: 10.7717/peerj.8693
|View full text |Cite
|
Sign up to set email alerts
|

Detection and visualization of abnormality in chest radiographs using modality-specific convolutional neural network ensembles

Abstract: Convolutional neural networks (CNNs) trained on natural images are extremely successful in image classification and localization due to superior automated feature extraction capability. In extending their use to biomedical recognition tasks, it is important to note that visual features of medical images tend to be uniquely different than natural images. There are advantages offered through training these networks on large scale medical common modality image collections pertaining to the recognition task. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…CXR modality-specific pretraining: Previous studies reveal that compared to using ImageNet weights, CXR modality-specific model pretraining results in learning meaningful modality-specific features that can be transferred to improve performance in a relevant classification task [ 40 , 46 ]. We performed CXR modality-specific pretraining using a selection of various publicly available CXR data collections to introduce sufficient diversity into the training process in terms of acquisition methods, patient population, and other demographics, to help the models broadly learn significant features from CXRs showing normal lungs and other pulmonary abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CXR modality-specific pretraining: Previous studies reveal that compared to using ImageNet weights, CXR modality-specific model pretraining results in learning meaningful modality-specific features that can be transferred to improve performance in a relevant classification task [ 40 , 46 ]. We performed CXR modality-specific pretraining using a selection of various publicly available CXR data collections to introduce sufficient diversity into the training process in terms of acquisition methods, patient population, and other demographics, to help the models broadly learn significant features from CXRs showing normal lungs and other pulmonary abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…The modality-specific knowledge would be relevant to be transferred to the CXR classification task, as compared to using the ImageNet weights from the natural image processing domain. A previous study [ 40 ] shows the benefits of using CXR modality-specific models retraining toward improving classification and localization performance and model generalization. During CXR modality-specific pretraining, the data are split at the patient level into 90% for training and 10% for testing.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly another study revealed that deep learning algorithms can help in the identification of lung opacities, enlargement of heart and pleural effusion on chest X-rays [16]. Due to the better automated feature extraction capability, the convolutional neural networks which have been trained on natural images turned out to be very successful in the classification of images [17]. The performance of convolutional neural network related to the imaging modalities with less human intervention has been found to be better than other conventional methods of machine learning [18].…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances reported in the literature use conventional hand-crafted feature descriptors/classifiers and DL models for classifying CXRs as showing normal lungs or pulmonary TB manifestations [ 6 , 7 ]. These studies reveal that the DL models outperform conventional methods toward medical image classification tasks, particularly CXR analysis [ 8 ]. The authors [ 7 ] used the publicly available TB datasets, including the Shenzhen TB CXR, the Montgomery TB CXR [ 6 ], the Belarus TB CXR [ 9 ], and another private TB dataset from the Thomas Jefferson University Hospital, Philadelphia.…”
Section: Introductionmentioning
confidence: 99%